The Simple Method to Assess Land Quality of Paddy Field Using Spectral, Soil pH and Statistical Regression Technique (Case Study of Paddy Field in Majalaya Subdistrict, Bandung Region) - Ghazali, Mochamad Firman; Harto, Agung Budi; Wikantika, Ketut (KnE Life Sciences, 2017)
Assessing land quality has important use in understanding the capability of soil in producing food. The area of paddy fields in Majalaya Subdistrict is located around the industrial zone and this situation is urgent to understand the land quality of paddy field due to the influence effect of industrial waste to its growth. A combination of regression model and Landsat 8 image to estimate soil pH distribution is used to predict the land quality. The result of this study is shown that the regression model of red and near infrared (NIR) band combination is used to predict soil pH has been successfully given the smallest error (RMSe) as the soil pH accuracy is 1.18 and related to the land quality assessment based on predicted soil pH is shown that in the whole area of paddy field has the acid situation of soil pH. Keywords: Spectral, Soil pH; Regression, Land Quality; Land Suitability